An integrated SWOT-fuzzy AHP-fuzzy TOPSIS analysis of various hydrogen energy storage options - Laveet Kumar (11460088) (2025)
The transition from fossil fuel dependency to low-carbon pathways and energy storage is heavily reliant on various options. Hydrogen is playing a pivotal role in achieving carbon-neutral targets and mitigating the intermittency issues of renewable energy resources. Despite its potential, the large-scale storage of H2 presents significant challenges. This research conducts a comprehensive integrated SWOT-Fuzzy AHP-Fuzzy TOPSIS analysis of various hydrogen energy storage (HES) options across the entire supply chain, from export site storage and loading to transportation and import site storage and unloading. The study evaluates liquid hydrogen (LH2), compressed gaseous hydrogen (CGH2), liquid organic hydrogen carriers (LOHCs), metal hydrides (MH), chemical hydrides (CH), carbon-based materials (CBM), and underground hydrogen (UH) storage as various HES options. From the analysis, CGH2 emerged as the most optimal technology for hydrogen storage and transport, ranking highest with a closeness coefficient (CCi) value of 0.287, due to its cost-effectiveness and well-established infrastructure. LH2 and LOHCs, ranking second and third respectively, are seen as strong contenders for large-scale, long-distance transport due to its high energy density. However, LH2 faces challenges because of its energy-intensive liquefaction process. MH, CH, and CBM, though promising in niche markets, face significant scalability and cost-effectiveness challenges, with MH ranking lowest in the study with a CCi value of 0.152, reflecting its limited practicality for large-scale applications. A sensitivity analysis was performed to validate the robustness of these rankings against moderate changes in expert weights. The findings provide decision-makers with valuable insights quantitatively into the strategic positioning of HES options within the evolving energy supply chain, guiding the choice of the most viable technology based on application needs. Other Information Published in: International Journal of Hydrogen Energy License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ijhydene.2025.150344